The Internal Rhythm in the Poetry of Al-Uqayshir Al-Asadi and its Impact on Constructing Ceaning- A Critical Study - Nsoor, Taiseer; Shahwan , Wafaa (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to explore the poetry of Al-Uqayshir Al-Asadi, focusing on the phenomenon of internal rhythm and its impact on meaning construction. Methods: This study employed a descriptive-analytical methodology, which involved observing the most important patterns of internal rhythm and examining their impact on meaning construction. This approach allowed the researcher to analyze musical phenomena within the framework of a critical view of the poetic text and track the effects of these artistic techniques. Results: The study revealed that internal rhythm was suitable for the poet’s psychological state, making the poem harmonious in form and content, complete in terms of rhythm and meaning. It stood out for its impactful musicality and elevated tone. The rhythmic structure complemented the semantic and emotional aspects, highlighting the functional aspect of the rhythmic structure in its expressive format. It also emphasized its semantic role associated with compositional and musical benefits. Conclusions: The study illuminated the role of internal rhythm in meaning construction and its relationship with semantic aspects in the poetry of Al-Uqayshir Al-Asadi. The study extracted various artistic skills related to sound, music, and poetic rhythm. Al-Uqayshir Al-Asadi’s poetry was distinguished by its impactful musicality and elevated tone, where the rhythmic structure worked in harmony with the semantic and emotional aspects. Repetition in his poetry served an important function in the poetic context, capturing the recipient’s attention to emphasize specific words. The study also revealed the functional aspect of the rhythmic structure in its expressive format, along with its semantic role associated with compositional and musical benefits.